STRENGTH ANALYSIS OF SELIS BRAND ELECTRIC BIKE FRAME THUNDER TYPE BMX 350 WATT USING ANSYS V17 SOFTWARE - Ruyanto Ruyanto; Yudi Samantha; Engkos Koswara (Universitas Majalengka, 2021)
Frame is one important component of the electric bicycle because it serves as the supporting components are installed, so that it becomes a unity that makes electric bikes can run. For static stress analysis was performed on an electric bicycle frame brands Selis thunder type 350 watts using ANSYS software V17 with amaximum static load of 1,200 kg. The purpose of this study was to determine the strength that is capable detained by order so that an unknown number of safety.After testing obtained amounted to 413.73 MPa maximum stress, maximum strain of 20.687x10-4 mm/mm , total maximum deformation of 95.99x10-2 mm and the safety factor at 0.6042.